Mitochondria in the maintenance of hematopoietic stem cells: new perspectives and opportunities - Filippi, Marie-Dominique (Blood, 2019)
The hematopoietic system produces new blood cells throughout life. Mature blood cells all derived from a pool of rare long-lived hematopoietic stem cells (HSCs) that are mostly quiescent but occasionally divide and self-renew to maintain the stem cell pool and to insure the continuous replenishment of blood cells. Mitochondria have recently emerged as critical not only for HSC differentiation and commitment but also for HSC homeostasis. Mitochondria are dynamic organelles that orchestrate a number of fundamental metabolic and signaling processes, producing most of the cellular energy via oxidative phosphorylation. HSCs have a relatively high amount of mitochondria that are mostly inactive. Here, we review recent advances in our understanding of the role of mitochondria in HSC homeostasis and discuss, among other topics, how mitochondrial dynamism and quality control might be implicated in HSC fate, self-renewal, and regenerative potential.